Food Security and Coping Strategies of Rural Household Livelihoods to Climate Change in the Eastern Cape of South Africa - Amoah, Laura Novienyo Abla; Simatele, Mulala Danny (Frontiers in Sustainable Food Systems, 2021)
Although governments across the globe have pledged resources and efforts to minimise the factors contributing to climate change, it is a concern that climate change continues to exert significant hardship on many rural communities of which South Africa is no exception. The Eastern Cape Province in South Africa is one of the driest provinces with prolonged water scarcity challenges. The purpose of this study is to investigate coping strategies adopted by the rural poor to build resilience against food insecurity. Primary data was collected from a total of 385 respondents in three rural communities using semi-structured questionnaires and interview. The findings suggest that farmers have been proactive in responding to climate change and food security. The study revealed that farmers are engaged in different coping strategies to ensure that there is enough food for the household. Although some of the coping strategies might assist, others would have severe consequences on the health of the population, especially children. Based on the findings, it is recommended that there should be regular engagement by the local municipality, the community and rural farmers on climate change events. The focus should be on the management of drought, heatwaves, flood, and soil erosion. The government within the local municipality should also focus on building a dam for rural farmers. The dam will serve as a reservoir of water for irrigation during drought.